The LAUGHTER THERAPY AS AN EFFORT TO HANDLE THE ANXIETY OF ELDERLY WHO EXPERIENCE ALONE IN OLD TIMES: LAUGHTER THERAPY AS AN EFFORT TO HANDLE THE ANXIETY OF ELDERLY WHO EXPERIENCE ALONE IN OLD TIMES - Hanim Nur Faizah; hyan oktodia basuki; mokhammad nurhadi; nailil hidayah; Alfiah Baituzzahro (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2023)
Background: Deteriorating health, decreased memory and loss of a spouse are examples of changes that make the elderly feel less self-respect. Elderly who experience separation from their partner will feel lonely. Long-term loneliness can lead to feelings of anxiety and hopelessness. Elderly who experience anxiety need ways to reduce anxiety as long as the elderly still experience loneliness. Purpose: This community service activity aims to provide information to the elderly in Jadi Village, Semanding about how to prevent anxiety about being alone in old age.Method: This community service activity uses the lecture and question and answer method. The lecture method is carried out by presenting material on efforts to prevent anxiety about loneliness in old age. While the question and answer method is done by asking participants about the material that has been delivered. Results: The results of this community service activity for the elderly found that as many as 80% of the counseling participants were able to understand and review the material that had been presented. Conclusion: Based on the community service activities that have been carried out, the participants are enthusiastic in receiving the whole series of events starting from the presentation of the material to questions and answers.